Cross‐cultural acceptability of interventions at the end of life in dementia: Video vignette study design and pilot evaluation (ERC CONT‐END WP1): Dementia — Cross‐cultural investigations. (7th December 2020) - van der Steen, Jenny T; Azizi, Bahar; Nakanishi, Miharu; Shinan‐Altman, Shiri; Mehr, David R; Radbruch, Lukas; Gaertner, Jan; Werner, Perla; Achterberg, Wilco P; Tilburgs, Bram; Smaling, Hanneke JA
Abstract: Background: In dementia, gradual cognitive and physical decline imply that control over life is typically lost. Interventions such as advance care planning (ACP), technology, or‐more extreme‐euthanasia can increase control over the end of life. So far, little is known about acceptability of these interventions from the perspective of persons with dementia and others involved. This study examines the cross‐cultural acceptability of four end‐of‐life interventions in dementia which contain an element of striving for control. We describe the development and pilot‐testing of video vignettes that explain interventions in a standardized manner. Method: The CONT‐END study Work Package 1 (NTR 7985) employs a cross‐sectional mixed‐methods design to assess acceptability of two types of ACP, technology use at the end of life and euthanasia, in three groups (persons with dementia, their family caregivers and physicians) in six countries (Netherlands, Japan, Israel, USA, Germany, Switzerland). Participants (150 per country) are interviewed about acceptability of the interventions. We will examine different acceptability by group and country and explore potentially associated factors such as coping style. We are pilot testing the acceptability, feasibility and burden of four video vignettes in persons with dementia and their family caregivers in the Netherlands. Result: We will demonstrate the video vignettes to explain the interventions. The first interviews indicate that persons with dementia and their family caregivers find the scripts of the video vignettes understandable, acceptable, feasible and not burdensome. They additionally commented on the subject matter in that they felt a current need for ACP on, for example, hospitalization, but would prefer to discuss need for technology and euthanasia later. We will present the pilot results and discuss hypotheses about acceptability of the four interventions in the three groups and six countries. Conclusion: The CONT‐END study will provide insight into cross‐cultural acceptability of interventions in dementia care from the perspective of persons with dementia, their family caregivers and physicians. This can help to better align interventions with preferences. The study will also result in a more fundamental understanding as to how and when having control at the end of life in dementia is perceived as beneficial or perhaps harmful.